Magnetic anisotropy induced in Nd16Fe76B8 by Hf additions - Rodríguez Torres, C. E. (2002)
Remanence, coercivity and maximum energy product (BH)max of Nd16Fe76-xHfxB8 (x = 0, 0.1, 0.2) magnets processed under different hydrogenation-disproportionation-desorption-recombination (HDDR) conditions, were studied. Vibrating sample magnetometry results showed that Hf-doped materials develop an important degree of anisotropy, especially for the case of solid-HDDR treatments at 800°C and 850°C, with the largest effect at 850°C. Maximum values of remanence and coercivity were observed for Hf-added samples S-HD at 850°C, and 900°C, respectively. The highest (BH)max value was also observed in S-HD 900°C Hf-added samples. These results are discussed in terms of the expected microstructure of the intermediate HD and final HDDR processed powders. © 2002 Elsevier Science B.V. All rights reserved.